Analysis of Vehicle Dynamic Behavior under Ballasted Track Irregularities in High-Speed Railway. (November 2015) - Cai, Xiaopei; Zhao, Lining; Lau, Albert Leong Lee; Tan, Shiyu; Cui, Rixin
Track irregularity is the main source of excitation that affects the dynamic characteristics of a railway vehicle. It has a significant influence on the stability and safety of a vehicle. In this study, a detailed vehicle–ballasted track dynamic model was established. The vehicle and ballasted track were modeled by multibody software SIMPACK and finite element software Abaqus respectively. The two models were then coupled by FEMBS which is an interface program between finite element (FE) analysis codes and SIMPACK. Based on the dynamic model, the vehicle dynamic behaviors of German and Chinese high-speed railways under ballasted track irregularity were analyzed. The results show that the vehicle dynamic behavior has random characteristics and responds differently to different types of single or combined irregularities. Comparatively, the vehicle dynamic responses acquired from a certain Chinese railway line measured on-site are slightly higher than those from GRSLI. It is also observed that the amplitude of vehicle dynamic responses increased linearly with the train's speed, and the dynamic response under the combined irregularity is slightly higher than the dynamic response under a single irregularity.